A Bibliometric Analysis of Financial Literacy and Financial Planning Research - Korip, Zahwa Muslimatul; Assyifa, Adzra Rania; Mantika, Syifa Unada; Kesuma, Muhammad Ramadhani; Ariswati, Lusiana Desy (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study presents a comprehensive bibliometric analysis of global research on financial literacy and financial planning published between 2000 and 2024. Using 452 Scopus-indexed documents, the study examines publication trends, journal distribution, and the conceptual structure of the field through keyword co-occurrence analysis using VOSviewer. The findings show a significant growth in research output, particularly after 2017, illustrating the increasing academic relevance of financial capability, financial behavior, and long-term financial well-being. The journal analysis identifies several influential sources, with the Journal of Financial Counseling and Planning emerging as the most productive outlet. Keyword mapping reveals six major thematic clusters that highlight core topics such as financial literacy, financial education, financial behavior, demographic and gender differences, decision-making, investment behavior, retirement planning, insurance, and behavioral biases. These clusters demonstrate the interdisciplinary development of the field, integrating psychological, demographic, and socio-economic dimensions. Overall, this study provides an updated conceptual landscape of financial literacy and financial planning research and offers valuable insights for researchers, educators, and policymakers. The results also underline the need for more holistic and context-specific financial education and policy initiatives, particularly in developing economies where financial literacy levels remain comparatively low.